The Effect of Nutritional Intake Education to Parents in Improving Feeding Patterns on The Growth of Stunted Children - Kalsum, Umi; Saputra, Zepri Ananda; Noorma, Nilam; Wahyuni, Emmy Putri (Eduvest - Journal of Universal Studies, 2025)
Stunting remains a serious health issue among toddlers in Indonesia, especially in areas with low parental education and socioeconomic status. One major cause is inadequate nutritional intake influenced by poor parental knowledge and feeding patterns. This study aims to analyze the effect of nutritional intake education on improving feeding practices and growth outcomes in stunted children aged 1–2 years in the working area of the Palaran Community Health Center. Using a quasi-experimental one-group pretest-posttest design, this research involved 11 stunted children selected through total sampling. Data collection included questionnaires, observation sheets, and child growth measurements, which were analyzed using paired t-tests and Wilcoxon tests with SPSS. Results showed significant improvements in feeding patterns and growth outcomes: height increased (p = 0.009) and weight improved significantly (p = 0.007) after educational interventions. Furthermore, parental knowledge improved from 54.5% to 100% in the ‘good’ category, and appropriate feeding patterns rose from 19% to 100%. These findings suggest that structured parental education can significantly enhance child nutrition and growth, supporting the implementation of targeted health programs. The study emphasizes the vital role of Posyandu in follow-up support and recommends expanding similar interventions to other under-resourced regions to reduce stunting rates nationally.